2021
DOI: 10.1002/ece3.8095
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the origins of invertebrate colonists in the Yangtze River Estuary with molecular markers: Implications for ecological connectivity

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
(129 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have suggested that aquatic and benthic signals from the Changjiang River Estuary can be observed in the Jiangsu coastal waters. For example, Li et al (2021) suggested that newly colonized Littorina brevicula on the Jiangsu Coast south of ~33.5°N originated from natural rock‐dwelling populations in the Changjiang River Estuary, indicating that the transport of larvae from the estuarine region played a key role in this colonization. It is notable that the plume transport along the Jiangsu Coast occurs at all water depths.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that aquatic and benthic signals from the Changjiang River Estuary can be observed in the Jiangsu coastal waters. For example, Li et al (2021) suggested that newly colonized Littorina brevicula on the Jiangsu Coast south of ~33.5°N originated from natural rock‐dwelling populations in the Changjiang River Estuary, indicating that the transport of larvae from the estuarine region played a key role in this colonization. It is notable that the plume transport along the Jiangsu Coast occurs at all water depths.…”
Section: Discussionmentioning
confidence: 99%
“…The abundant Yangtze River‐derived mud deposit on the inner shelf, combined with contribution from other rivers, has created a large delta plain (3 × 10 4 km 2 ) and a muddy tidal flat along the coastline from the Northern Jiangsu Province (~35° N) to the Southern Zhejiang Province (30° N) over about 500 km wide (Zhu et al., 2008). A few studies have revealed the Yangtze River Estuary as a physical barrier for several intertidal molluscs (Dong et al., 2012; Li et al., 2021; Ni et al., 2015; Wang et al., 2015) or macroalga (Cheang et al., 2010) due to the unusual substrate and/or the effect of freshwater discharge. As Z. japonica could tolerate short‐term exposure to zero salinity in situ (Kaldy & Shafer, 2013; Shafer et al., 2011) and survive in very muddy bottom (Zhang, Lin, et al., 2019), neither the salinity nor the substrate conditions seem to have limited the survival of Z. japonica in the Yangtze River Estuary.…”
Section: Discussionmentioning
confidence: 99%
“…et al, 2008). A few studies have revealed the Yangtze River Estuary as a physical barrier for several intertidal molluscs (Dong et al, 2012;Li et al, 2021;Ni et al, 2015;Wang et al, 2015) or macroalga (Cheang et al, 2010) due to the unusual substrate and/or the effect of freshwater discharge. As Z. japonica could tolerate short-term exposure to zero salinity in situ (Kaldy & Shafer, 2013;Shafer et al, 2011) and survive in very muddy bottom (Zhang, Lin, et al, 2019), neither the salinity nor the substrate conditions seem to have limited the survival of Z. japonica in the Yangtze River Estuary.…”
Section: During Pleistocene Glaciation Episodes the Sea Level In The ...mentioning
confidence: 99%